Peningkatan Kualitas Produk UKM â€œPeyek Bunderâ€ Melalui Introduksi Teknologi Tepat Guna Spinner - Kusnandar Kusnandar; Mohd. Harisudin; Erlyna Wida Riptanti; Isti Khomah; Nuning Setyowati; Rr. Aulia Qonita (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service activity aims to improve the quality of Peyek Bunder by introducing a spinner in the production process of small micro enterprises (SMEs) partnered with